SPREAD OF RUSSIAN AMERICA ORTHODOXY AT THE END OF XVIII - FIRST HALF OF XIX CENTURIES - Elena Galkina (Гуманитарные и юридические исследования)
The article is devoted to the establishment of Russian Orthodoxy in America in the late XVIII - middle XIX centuries. The desire to gain huge benefits forced many Russians to go to distant lands, including Russian America, and undertake difficult trips involving risks and danger. The official date of foundation of the Orthodox Church in North America was considered September 24, 1794, and this was due to the arrival of the Orthodox mission to the island of Kadjak under the leadership of Archimandrite Joasaph. The further Orthodox mission was connected with the activities of St. Innocent (I. E. Veniaminov), who did a great job for spiritual enlightenment of the indigenous peoples of Alaska and the Aleutian Islands. The difficulties of the mission were determined by the complexities of everyday life on distant islands, and relations with Aborigines, often the cruel treatment of Russians with the indigenous population. Therefore, the author's attention is focused on complicated relationships of Russians with aborigines of Russian America in their religious and spiritual enlightenment. The sale of Alaska in 1867 to the United States changed the dominant status of the right-glorious church in Russian America, which, having not received the support of the new American authorities lost its influence on the indigenous population. Protestantism ousted Orthodoxy in Russian America, but not completely, because the Orthodox Church continues its missionary activity to this day.